1979
DOI: 10.1111/j.1600-0773.1979.tb02292.x
|View full text |Cite
|
Sign up to set email alerts
|

The Binding of CTAB, a Cationic Surfactant, to the Rat Erythrocyte Membrane

Abstract: Absrract: The adsorption of CTAB (cetyltrimethylammonium bromide) to the rat erythrocyte membrane was studied by determining the electrophoretic mobility of erythrocytes treated with CTAB and by SDS polyacrylamide electrophoresis of membrane proteins from erythrocytes treated with IT-CTAB. At low concentrations of CTAB there was only a small reduction in the electrophoretic mobility of the erythrocytes. At lytic concentrations the electrophoretic mobility of the erythrocytes was markedly reduced. Alterations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Because of their importance as antiseptic agents, the actions of surface-active alkyltrimethylammonium salts on cells have been subjected to many studies. Several authors have suggested that the principal point of attack of cationic surfactants is the lipid bilayer of the plasma membrane (Hooghwinkel et al 1965;Kondo & Tomizawa 1966;Reman et al 1969;Isomaa et al 1979). The surfactant molecules are assumed to penetrate into the lipid bilayer which they tend t o break up into localized micellar arrangements (Haydon & Taylor 1963;Seufert 1965).…”
mentioning
confidence: 99%
“…Because of their importance as antiseptic agents, the actions of surface-active alkyltrimethylammonium salts on cells have been subjected to many studies. Several authors have suggested that the principal point of attack of cationic surfactants is the lipid bilayer of the plasma membrane (Hooghwinkel et al 1965;Kondo & Tomizawa 1966;Reman et al 1969;Isomaa et al 1979). The surfactant molecules are assumed to penetrate into the lipid bilayer which they tend t o break up into localized micellar arrangements (Haydon & Taylor 1963;Seufert 1965).…”
mentioning
confidence: 99%